Microglial microvesicles secretion and intercellular signalling - Turola, Elena; Furlan, Roberto; Bianco, Fabio; Matteoli, Michela; Verderio, Claudia (Frontiers in Physiology, 2012)
Microvesicles (MVs) are released from almost all cell brain types into the microenvironment and are emerging as a novel way of cell-to-cell communication. This review focuses on MVs discharged by microglial cells, the brain resident myeloid cells, which comprise ∼10–12% of brain population. We summarize first evidence indicating that MV shedding is a process activated by the ATP receptor P2X7 and that shed MVs represent a secretory pathway for the inflammatory cytokine IL-β. We then discuss subsequent findings which clarify how IL-1 β can be locally processed and released from MVs into the extracellular environment. In addition, we describe the current understanding about the mechanism of P2X7-dependent MV formation and membrane abscission, which, by involving sphingomyelinase activity and ceramide formation, may share similarities with exosome biogenesis. Finally we report our recent results which show that microglia-derived MVs can stimulate neuronal activity and participate to the propagation of inflammatory signals, and suggest new areas for future investigation.